Fluency and Reading Comprehension in Typical Readers and Dyslexics Readers - Simone A. Capellini (Frontiers Research Topics, 2018)
Reading involves decoding and comprehension components and, to become efficient, it requires a large number of cognitive and linguistic processes. Among those, the phonological awareness, the alphabetic principle, the decoding, the fluency, the lexical development and the text comprehension development. The reading comprehension is strongly related with the development of vocabulary, oral language, linguistic skills, memory skills and ability to make inferences, and the world experiences of each individual. These processes become important only when the professional needs to deal with students presenting difficulties in learning how to read. The difficulty using the knowledge of conversion rules between grapheme and phoneme to the word reading construction characterizes the dyslexia, which is a specific learning disorder with a neurological source. These difficulties presented by students with dyslexia interfere in their learning process impairing the learning development. Knowing and following the reading development and its processes, as well as obtaining the punctuation of fluency abilities and students comprehension allow us to understand what happens when the student presents difficulties to read. This could help in the identification of learning disabilities and in the development of intervention programs.